Preoperative albumin levels predict prolonged postoperative ileus in gastrointestinal surgery - Liang, Wen-Quan (World J Gastroenterol, 2020)
BACKGROUND: Prolonged postoperative ileus (PPOI) is a prolonged state of “pathological” gastrointestinal (GI) tract dysmotility. There are relatively few studies examining the influence of preoperative nutritional status on the development of PPOI in patients who underwent GI surgery. The association between preoperative albumin and PPOI has not been fully studied. We hypothesized that preoperative albumin may be an independent indicator of PPOI. AIM: To analyze the role of preoperative albumin in predicting PPOI and to establish a nomogram for clinical risk evaluation. METHODS: Patients were drawn from a prospective hospital registry database of GI surgery. A total of 311 patients diagnosed with gastric or colorectal cancer between June 2016 and March 2017 were included. Potential predictors of PPOI were analyzed by univariate and multivariable logistic regression analyses, and a nomogram for quantifying the presence of PPOI was developed and internally validated. RESULTS: The overall PPOI rate was 21.54%. Advanced tumor stage and postoperative opioid analgesic administration were associated with PPOI. Preoperative albumin was an independent predictor of PPOI, and an optimal cutoff value of 39.15 was statistically calculated. After adjusting multiple variables, per unit or per SD increase in albumin resulted in a significant decrease in the incidence of PPOI of 8% (OR = 0.92, 95%CI: 0.85-1.00, P = 0.046) or 27% (OR = 0.73, 95%CI: 0.54-0.99, P = 0.046), respectively. Patients with a high level of preoperative albumin (≥ 39.15) tended to experience PPOI compared to those with low levels (< 39.15) (OR = 0.43, 95%CI: 0.24-0.78, P = 0.006). A nomogram for predicting PPOI was developed [area under the curve (AUC) = 0.741] and internally validated by bootstrap resampling (AUC = 0.725, 95%CI: 0.663-0.799). CONCLUSION: Preoperative albumin is an independent predictive factor of PPOI in patients who underwent GI surgery. The nomogram provided a model to screen for early indications in the clinical setting.